Distinct disinhibitiory circuits differentially modulate the multisensory integration in a feedforward network - Lee, Seungyoun; Kang, Kyujin; Yoon, Yebeen; Han, Jae-Ho; Jang, Hyun Jae (The proceedings of the CNS*2025 meeting, 2025)
Multisensory integration is a fundamental neural process that combines simultaneously presented unisensory inputs into a unified perception. For effective multisensory processing, cross-modal integration via neural network should be dynamically modulated spanning cortical and subcortical regions in vivo[1,2]. One such mechanism is the disinhibitory circuit gating local information flow by inhibiting other inhibitory neurons. However, it is unclear whether disinhibitory circuits modulate multisensory integration locally or via long-range projections[3,4]. Therefore, we investigated how distinct disinhibition architectures differentially modulate long-range cross-modal integration, such as between the primary auditory cortex (A1) and the visual cortex (V1)[5]. To test this, we developed a computational feedforward network model incorporating in vivo-recorded spike trains from A1 and V1. The model consists of two four-layer columns, each representing a different sensory modality, converging onto an output layer (LOUT). Neurons were modeled as single-compartment Hodgkin-Huxley-type neurons, capturing the electrophysiological properties of pyramidal (PYR), somatostatin-positive (SST+), and vasoactive intestinal polypeptide-positive (VIP+) neurons. The disinhibitory circuit was modeled such that VIP+ neurons inhibit SST+ neurons, which in turn inhibit PYR neurons. The first layer of each column received spike trains recorded in vivo A1 and V1 during pure-tone and grating stimulation as inputs. We first assessed disinhibitory circuits in multisensory integration. A network with disinhibition exhibited higher mutual information (MIrate) between stimulus variables and firing rates of Lout than one without, indicating enhanced integrated information transmission. To investigate how disinhibition-mediated different inhibitory circuit modulates multisensory integration, we differentiated SST+ inhibitory circuits by intra-columnar feedback (intra-FBI), intra-columnar feedforward (intra-FFI), and cross-columnar feedforward inhibition (cross-FFI). When we fed in vivo spike patterns into these models, we found that MIrate was highest in intra-FFI, whereas MI for spike timing was highest with intra-FBI, implying distinct roles in neural coding. Our results demonstrate that disinhibitory circuits facilitate multisensory integration by dynamical modulation of long-range cross-modal interactions between A1 and V1. Specifically, our findings reveal that the intra-FFI circuit was associated with firing rates whereas intra-FBI circuit enhanced information encoded in spike timings. This suggests that distinct disinhibitory circuits selectively integrate multisensory information through different neural coding strategies. Taken together, these findings indicate that distinct disinhibitory network motifs dynamically modulate multisensory integration and may serve as a key mechanism in in vivo multisensory processing.